Neurotoxic microglia promote TDP-43 proteinopathy in progranulin deficiency - Zhang, Jiasheng (Nature, 2020)
Aberrant aggregation of RNA binding protein TDP-43 in neurons is a hallmark of frontotemporal lobar degeneration caused by progranulin haploinsufficiency(1,2). However, the mechanism leading to TDP-43 proteinopathy remains unclear. Here we use single-nucleus RNA-sequencing (snRNA-seq) to show that progranulin deficiency promotes microglial transition from a homeostatic to disease-specific state that causes endolysosomal dysfunction and neurodegeneration. These defects persist even when Grn(−/−) microglia are cultured ex vivo. In addition, snRNA-seq reveals selective loss of excitatory neurons at disease end-stage, characterized by prominent nuclear and cytoplasmic TDP-43 granules and nuclear pore defects. Remarkably, conditioned media from Grn(−/−) microglia is sufficient to promote TDP-43 granule formation, nuclear pore defects and cell death in excitatory neurons via the complement activation pathway. Consistent with these results, deleting C1qa and C3 mitigates microglial toxicity, and rescues TDP-43 proteinopathy and neurodegeneration. These results uncover previously unappreciated contributions of chronic microglial toxicity to TDP-43 proteinopathy during neurodegeneration.